2021
DOI: 10.3390/s21186042
|View full text |Cite
|
Sign up to set email alerts
|

Textile-Based Sensors for Biosignal Detection and Monitoring

Abstract: Biosignals often have to be detected in sports or for medical reasons. Typical biosignals are pulse and ECG (electrocardiogram), breathing, blood pressure, skin temperature, oxygen saturation, bioimpedance, etc. Typically, scientists attempt to measure these biosignals noninvasively, i.e., with electrodes or other sensors, detecting electric signals, measuring optical or chemical information. While short-time measurements or monitoring of patients in a hospital can be performed by systems based on common rigid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 131 publications
1
26
0
Order By: Relevance
“…The ECG and, as a simpler measurement with reduced information value, the pulse rate, are among the most important biosignals, enabling evaluation of one of the essential signals derivable from the human body. Similar to a previous study in which most textile-based sensors were found to be related to ECG measurements [ 14 ], a majority of biosignal electronics deals with measuring ECG and pulse.…”
Section: Ecg and Pulse Measurementssupporting
confidence: 63%
See 1 more Smart Citation
“…The ECG and, as a simpler measurement with reduced information value, the pulse rate, are among the most important biosignals, enabling evaluation of one of the essential signals derivable from the human body. Similar to a previous study in which most textile-based sensors were found to be related to ECG measurements [ 14 ], a majority of biosignal electronics deals with measuring ECG and pulse.…”
Section: Ecg and Pulse Measurementssupporting
confidence: 63%
“…As glued electrodes for ECG measurements and rigid systems for other measurements are uncomfortable in long-term usage, many approaches to integrate electrodes into clothes or to prepare textile-based electrodes have been reported during the last decades [ 11 , 12 , 13 , 14 , 15 , 16 ]. While these attempts result in increasingly reliable soft textile electrodes and sensors for the detection of ECG and many other biosignals, data evaluation still necessitates either rigid electronics or highly specialized flexible electronics, which are not available for all research groups in the textile or medical area [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Flexible sensors have been attracting great attention due to their potential to be used as wearable chemical sensors [23,24] in the fields of sports [25,26] and health [27], medicine and occupational safety [28]. Hazard identification by monitoring in real-time the body status and the surrounding environment, allows for fast response in order to take countermeasure against potential damage [29][30][31].…”
mentioning
confidence: 99%
“…The nanofiber mats prepared by electrospinning and carbon nanofiber mats are widely used in the fields of filtration, separation, sensors, catalyst support, energy storage, biomedicine, shielding from radiation, etc., [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The application of carbon nanofibers in the field of sensing elements is based on their electronic transport properties, which are modulated by the physical-chemical interaction of the sensing element [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study by Döpke et al, PAN/magnetite nanofiber mats were prepared and the magnetic properties were investigated [ 2 ]. Here, networks of magnetic nanofibers with beads that can be used to transport data in the form of domain walls moving along them and combined with objects that could be used to store data and transport [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 …”
Section: Introductionmentioning
confidence: 99%